Penolakan Umat terhadap Risalah Kenabian dan Relevansinya dengan Penolakan Reformasi Hukum Keluarga di Mesir - Muhammad Hadyan Wicaksana; Ahmad Rezy Meidina (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
This paper discusses the prophetic treatises carried out by the people in relation to changes in family law reform in Egypt. The culture that has been passed down from generation to generation since the time of the ancestors will take root in the heart, so that the embedded doctrine is difficult to remove, so it takes a harder effort to accept the changing times. This research includes a literature study (Library Research), which is descriptive-analytical, using a historical-sociological approach. The rejection that occurs in the prophetic treatise is the same as the legal changes made by the Egyptian government, the similarities between the two are that they do not want to accept changes that occur in society, still hold on to the old culture adopted by their ancestors and still hold onto the animation culture. The basic reason for not accepting the change is because of the lack of understanding of what it will bring and the absence of an open mind (open thinking) by accepting input which is then discussed. Keywords: Prophetic Tracts, Reform of Family Law, Egypt